Parental social support and early childhood prevention in contexts of adversity: The perspective of early years’ educators and mental health professionals in Brazil - Novaes, Marcelly de Brito (2017)
This qualitative and exploratory study aims to understand the perceptions of professionals, who work in a day care centre and a mental health service for children (Psychosocial Attention Centre for Childhood – CAPSi), about the formal parental social support theyoffer within contexts of adversity. It also aims to understand the perceptions of parental exercise in Brazilian culture by those professionals.The participant institutions serve families in adversity settings or residents of favelas in Rio de Janeiro city, Brazil. Semi structured interviews and participant observation were done during nine weeks. Seventeen child care professionals (helpers) were interviewed, six in the day care centre and 11 in the CAPSi. The helpers relate the difficulties on the intervention process to the families’ socioeconomic context. Negative and coercive parental attitudes are considered to be normal by the professionals within the scope of the Brazilian culture. Professional social support is a need for helpers of formal parental support to families in socioeconomic’ conditions of adversity in Brazil.